Sistema de evaluación en el desarrollo de competencias genéricas en estudiantes del IV ciclo de la especialidad de ciencias sociales de la Universidad Nacional de la Amazonía Peruana, Iquitos 2024 - Cardenas Ruiz, July (2025)
The objective of the study was: To determine the evaluation system in the development of generic competencies in students of the fourth cycle of the specialty of social sciences at the National University of the Peruvian Amazon, Iquitos 2024. The study is a quantitative experimental and pre-experimental design with 1 group. We worked with a sample of 21 students of the IV cycle of Social Sciences, of the FCEH of the UNAP to whom a pre-test was applied in the first instance through a previously validated questionnaire survey, to later carry out a post-test and collect the definitive information, which in the before is Low and in the after Regular. With a = Alpha = 0.05 = 5% and standardized Z to contrast paired samples in the observation of the development of competences, p-value = 0.000 = 0.0%. HO is rejected if: p -value < 0.05 (p = bilateral asymptotic significance). 0.0% error the evaluation system improves significantly and at 95% confidence the research hypothesis is approved: The evaluation system has a positive effect on the development of generic competencies in students of the IV Cycle of the specialty of CC. SS of the FCEH – UNAP 2024.